Kemitraan Multi Pihak Dalam Penanggulangan Kemiskinan (Studi Kasus Program Gandeng Gendong Kota Yogyakarta) - Linda, Rusna Eva; Hadiwijoyo, Suryo Sakti; ., Daru Purnomo (Kolaborasi : Jurnal Administrasi Publik, 2024)
Gandeng Gendong Program is a program to solve the issue of poverty in the city of Yogyakarta. In the implementation of activities, the governance structure of the Gandeng Gendong program involves 5K which consists of the Village (Yogyakarta City Residents), Campus (Tridarma), Yogyakarta City Government, Corporate (private), and Community. The purpose of research is to analyze Multi-Party partnerships and the implementation of the Gandeng Gendong program in poverty reduction in the city of Yogyakarta. This research uses a descriptive qualitative method. The results of this study show that in Giddens' structural theory, the relationship between "Gandeng Gendong Program" and "5K '' is a social practice. Especially if "Gandeng GendongProgram '' is understood as a structure and "5K" as an agency. The Gandeng Gendong Program uses a structure of legitimacy that can be in the form of social norms, values and standards. The structure formed is an agreement in the form of an MoU and has forums and work mechanisms that have been stated in the Yogyakarta City Regent Regulation No.23/2018. The Gandeng Gendong program for poverty alleviation uses a multi-party join program collaboration. There is a collaborative relationship between 5K partners who run the Gandeng Gendong program. Implementation of the Gandeng Gendong Program through Nglarisi activities in Jogja Smart Service (JSS) for MSMEs providing food and beverages.